A comparative study on the mechanical behavior of S355J2 steel repair-welded joints. (June 2023) - Yu, Banglong; Chen, Zhihao; Wang, Ping; Song, Xiaoguo
Abstract: The mechanical behavior of repair-welded joints was particularly important for the service safety of steel structures. The microstructure and mechanical behavior of S355J2 steel base metal, welded and repair-welded joints were investigated in this paper. The low cycle fatigue tests on S355J2 steel base metal, welded, and repair-welded joints were conducted fully reversed with strain amplitudes varying from ±0.2% to ±1.1%. The results found that the microhardness of repair-welded joints decreased by about 20 HV with the growth in grain size of weld metal and heat-affected zone. Both elongations of welded and repair-welded joints were reduced by about 25.1% compared with the base metal. Considering the cyclic loading behavior, S355J2 steel base metal, welded, and repair-welded joints exhibited continuously softened, while the repair-welded joints exhibited a greater amount of softening than welded joints. Based on the Coffin-Manson equation, the decreased ratio of permissible total strain amplitude of repair-welded joints was significantly higher for medium and high cycle fatigue (> 10 4 ) compared to low cycle fatigue (< 10 4 ). The low cycle fatigue fracture surface shows that the defects in the repair-welded joints were the fatigue crack initiation position, but the S355J2 steel base metal and welded joints were initiated on the surface of the specimen. Highlights: The microhardness of repair-welded joints reduce with the grain size of HAZ growth. The defects in the repair-welded joints become the crack initiation location. The amount of softening of repair-welded joints are larger than that of welding. At ELCF, joint's life is similar due to ultimate tensile strength.